Marital Dissatisfaction among Married Depressed Women: A Cross Sectional Study in a University Hospital of Bangladesh - Ahmed, Mohammad Farid Uddin; Masud, Mahadi; Podder, Palash Kumar; Andalib, Nuzhat; Ferdoush, Kazi Azajul; Forhad, Md Mejbaul Khan; Khan, Md Rashed; Huq, Mohammad Fazlul; Morshed, Mamun; Shahinuzzaman, Mridha Mohammad; et al. (Faridpur Medical College Journal, 2026)
Background: Marital dissatisfaction is prevailing in the family and is negatively affecting the couples as well as the society. Women are more vulnerable to develop depression when they are martially dissatisfied. Materials & Methods: This cross-sectional observational study was conducted into the outpatient department (OPD) of psychiatry, Bangladesh Medical University (BMU), Dhaka from July’18 to December’18 to identify the proportion of marital dissatisfaction among married depressed women and to determine the association of socio demographic variables with marital dissatisfaction. Total 150 adult ( 18 years or more ) married depressed women were taken for this study. Results: In this study, 74% married depressed women were dissatisfied in their marital life, the age group 20-30 years having the highest dissatisfaction rate (52.25%), education has a significant and positive association with satisfaction, house wives were mostly dissatisfied (88.29%), marital duration had the strongest association with marital quality. Dissatisfaction rate was higher in settle than affair marriage, the respondents in nuclear family having the higher dissatisfaction rate than those in extended and joined family, women who had problem solving skill experiences more satisfaction than those who were not capable of problem solving. Conclusion: This can be concluded that the marital dissatisfaction is common among married depressed women. Faridpur Med. Coll. J. 2026;21(1):38-44